A Chiral Halogen‐Bonding [3]Rotaxane for the Recognition and Sensing of Biologically Relevant Dicarboxylate Anions. Issue 2 (8th December 2017) - Lim, Jason Y. C.; Marques, Igor; Félix, Vítor; Beer, Paul D.
Abstract: The unprecedented application of a chiral halogen‐bonding [3]rotaxane host system for the discrimination of stereo‐ and E / Z geometric isomers of a dicarboxylate anion guest is described. Synthesised by a chloride anion templation strategy, the [3]rotaxane host recognises dicarboxylates through the formation of 1:1 stoichiometric sandwich complexes. This process was analysed by molecular dynamics simulations, which revealed the critical synergy of halogen and hydrogen bonding interactions in anion discrimination. In addition, the centrally located chiral ( S )‐BINOL motif of the [3]rotaxane axle component facilitates the complexed dicarboxylate species to be sensed via a fluorescence response. Abstract : The discrimination between dicarboxylate stereo‐ and geometric isomers by a chiral halogen‐bonding [3]rotaxane can be monitored in terms of the fluorescence response. Computational modelling studies revealed the critical synergy between the axle of the rotaxane host and macrocycle components in achieving dicarboxylate guest selectivity.